A systematic approach for an application of personnel selection in assembly line balancing problem. (6th July 2017) - Efe, Burak; Kurt, Mustafa
Abstract: This paper aims to present a novel systematic approach to personnel selection. The contributions of this paper are on the multicriteria decision‐making problem and the assembly line balancing problem related to personnel selection. This paper presents a novel method, which is the possibility degree based TOPSIS (technique for order preference by similarity to ideal solution) method with interval type‐2 trapezoidal fuzzy (IT2TrF) numbers, as an extension of the TOPSIS method for the personnel selection problem. This paper presents the possibility mean value and possibility degree measures instead of distance measures in current TOPSIS to define a comparative index. The closeness coefficient based on the possibility degree of each alternative is calculated according to the approximate positive and negative ideal solutions. The subjective judgments of the decision makers are aggregated to calculate the weights of the criteria. The weights based on the IT2TrF number are input into IT2TrF number based the TOPSIS phase to rank the alternatives. The proposed method is applied to evaluate the personnel selection in an assembly line of a textile firm after the closeness coefficient of each personnel is determined.